Mitochondrial Heteroplasmy and the Evolution of Insecticide Resistance: Non-Mendelian Inheritance in Action - Van Leeuwen, Thomas; Vanholme, Bartel; Van Pottelberge, Steven; Van Nieuwenhuyse, Pieter; Nauen, Ralf; Tirry, Luc; Denholm, Ian (Proceedings of the National Academy of Sciences - PNAS, 2008)
Genes encoded by mitochondrial DNA (mtDNA) exist in large numbers per cell but can be selected very rapidly as a result of unequal partitioning of mtDNA between germ cells during embryogenesis. However, empirical studies of this "bottlenecking" effect are rare because of the apparent scarcity of heteroplasmic individuals possessing more than one mtDNA haplotype. Here, we report an example of insecticide resistance in an arthropod pest (Tetranychus urticae) being controlled by mtDNA and on its inheritance in a heteroplasmic mite strain. Resistance to the insecticide bifenazate is highly correlated with remarkable mutations in cytochrome b, a mitochondrially encoded protein in the respiratory pathway. Four sites in the Qₒ site that are absolutely conserved across fungi, protozoa, plants, and animals are mutated in resistant mite strains. Despite the unusual nature of these mutations, resistant mites showed no fitness costs in the absence of insecticide. Partially resistant strains, consisting of heteroplasmic individuals, transmit their resistant and susceptible haplotypes to progeny in highly variable ratios consistent with a sampling bottleneck of ≈180 copies. Insecticide selection on heteroplasmic individuals favors those carrying resistant haplotypes at a frequency of 60% or more. This combination of factors enables very rapid evolution and accounts for mutations being fixed in most field-collected resistant strains. The results provide a rare insight into non-Mendelian mechanisms of mitochondrial inheritance and evolution, relevant to anticipating and understanding the development of other mitochondrially encoded adaptations in arthropods. They also provide strong evidence of cytochrome b being the target site for bifenazate in spider mites.